2018
DOI: 10.1016/j.jhydrol.2018.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biotic and abiotic factors on inter- and intra-event variability in stemflow rates in oak and pine stands in a Mediterranean mountain area

Abstract: Stemflow, despite being a small proportion of the gross rainfall, is an important and understudied flux of water in forested areas. Recent studies have highlighted its complexity and relative importance for the understanding of soil and groundwater recharge. Stemflow dynamics offer an insight into the rain water that is stored and released from the stems of trees to the soil. Different attempts have been made to understand the variability of stemflow under different types of vegetation, but rather few have foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 42 publications
8
53
0
Order By: Relevance
“…Ikawa et al (2011) ; and d-excess difference between sequential throughfall and sequential rainfall samples higher than for needles. Cayuela et al (2018) found that, above 20 mm of rainfall, funnelling ratios for both species no longer increased.…”
Section: Intrastorm Isotopic Composition Of Rainfall and Throughfallmentioning
confidence: 88%
See 3 more Smart Citations
“…Ikawa et al (2011) ; and d-excess difference between sequential throughfall and sequential rainfall samples higher than for needles. Cayuela et al (2018) found that, above 20 mm of rainfall, funnelling ratios for both species no longer increased.…”
Section: Intrastorm Isotopic Composition Of Rainfall and Throughfallmentioning
confidence: 88%
“…For Scots pine, Llorens and Gallart (2000) found that the specific storage capacity of stems was six times higher than for needles. Cayuela et al (2018) found that, above 20 mm of rainfall, funnelling ratios for both species no longer increased.…”
Section: Intrastorm Isotopic Composition Of Rainfall and Throughfallmentioning
confidence: 88%
See 2 more Smart Citations
“…Functional traits, such as life form (tree, shrubs, herbaceous), life habits (evergreen, semi-deciduous, and deciduous), branching architecture, leaf area, specific leaf area, or hydraulic conductivity, establish differences in the structure of a forest and, consequently, in the soil water balance in several vegetation types [21]. Forest canopy characteristics also determine the volume of water flows across a vegetation canopy, such as interception, stemflow, and throughfall [22]. Soil characteristics, such as soil bulk density, soil particle size, porosity, field capacity content, or wilting point moisture content, will also determine water availability for plants and, therefore, the water flows from the surface to the water table [23].…”
Section: Plant Functional Characteristics and Strategy To Cope With Dmentioning
confidence: 99%